FORT WAYNE, CHARTER AND REVISED ORDINANCES, ch. 31, § 17 (Sentinel Book and Job Office 1887). - (:unkn) unknown (General Publisher, 1887)
It shall be unlawful for any person to fire or discharge any common gun, fowling piece, pistol or firearms of any description, or fire, or explode or set off any squib, cracker, or any other thing containing powder, or other combustible or explosive material, without permission from the Common Council, or written permission from the Mayor
--
Keywords: DISCHARGE